A refined ecological risk assessment for California red‐legged frog, Delta smelt, and California tiger salamander exposed to malathion. (19th December 2017) - Clemow, Yvonne H; Manning, Gillian E; Breton, Roger L; Winchell, Michael F; Padilla, Lauren; Rodney, Sara I; Hanzas, John P; Estes, Tammara L; Budreski, Katherine; Toth, Brent N; Hill, Katie L; Priest, Colleen D; et al.
ABSTRACT: The California red‐legged frog (CRLF), Delta smelt (DS), and California tiger salamander (CTS) are 3 species listed under the United States Federal Endangered Species Act (ESA), all of which inhabit aquatic ecosystems in California. The US Environmental Protection Agency (USEPA) has conducted deterministic screening‐level risk assessments for these species potentially exposed to malathion, an organophosphorus insecticide and acaricide. Results from our screening‐level analyses identified potential risk of direct effects to DS as well as indirect effects to all 3 species via reduction in prey. Accordingly, for those species and scenarios in which risk was identified at the screening level, we conducted a refined probabilistic risk assessment for CRLF, DS, and CTS. The refined ecological risk assessment (ERA) was conducted using best available data and approaches, as recommended by the 2013 National Research Council (NRC) report "Assessing Risks to Endangered and Threatened Species from Pesticides." Refined aquatic exposure models including the Pesticide Root Zone Model (PRZM), the Vegetative Filter Strip Modeling System (VFSMOD), the Variable Volume Water Model (VVWM), the Exposure Analysis Modeling System (EXAMS), and the Soil and Water Assessment Tool (SWAT) were used to generate estimated exposure concentrations (EECs) for malathion based on worst‐case scenarios in California. Refined effects analyses involved developing concentration–response curves for fish and species sensitivity distributions (SSDs) for fish and aquatic invertebrates. Quantitative risk curves, field and mesocosm studies, surface‐water monitoring data, and incident reports were considered in a weight‐of‐evidence approach. Currently, labeled uses of malathion are not expected to result in direct effects to CRLF, DS or CTS, or indirect effects due to effects on fish and invertebrate prey. Integr Environ Assess Manag 2018;14:224–239. © 2017 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals, Inc. on behalf of Society of Environmental Toxicology & Chemistry (SETAC) Key Points: A probabilistic risk assessment using refined exposure modeling was conducted on 3 endangered species residing in California, USA. Based on all lines of evidence, malathion is not expected to result in direct effects to the species, or indirect effects due to effects on fish and invertebrate prey.